Applicability of tactile memory examination as an option to visual-and verbal-based batteries - Arambula, Omar Gurrola [UNESP]; Padovani, Flavia Helena Pereira [UNESP]; Corrente, Jose Eduardo [UNESP]; Schelp, Andreas Batista; Sanches, Felipe Jacques [UNESP]; Amorim, Rogerio Martins [UNESP]; Schelp, Arthur Oscar [UNESP] (FapUNIFESP (SciELO), 2021)
The validity and applicability of tactile battery tests for the diagnosis and medical follow-up of patients with Alzheimer’s disease and other dementia syndromes do not have their usefulness well understood in clinical practice. While haptic abilities in older individuals receive less attention, in earlier stages of human life they are well focused on. There are even fewer studies on tactile memory, including episodic memory of demented individuals with or without sensorial limitations. The applicability of a new haptic memory battery was evaluated in patients with Alzheimer’s disease with mild or moderate commitment. Objective: The aim of this study is to apply a battery based on tactile perception, recognition, and recollection of everyday objects in patients with Alzheimer’s disease, testing tactile delayed recall memory discrimination and late recognition to compare validated visual and verbal tests. Methods: Tactile-, visual-, and verbal-based memory performance was registered in 21 patients diagnosed with Alzheimer’s disease. Results: Except for tactile identification, it showed that there was a close relationship between the three sensory modalities of memory, with an apparent better performance of tactile incidental memory and recognition compared with the test with pictures. Conclusions: The haptic evaluation of memory demonstrated applicability in the evaluation of memory dysfunction in patients with Alzheimer’s disease. Further studies are needed to establish the sensibility and specificity of the proposed test that had a small sample size and many limitations.
A aplicabilidade da avalição da memória tátil como uma opção para as baterias visuais a verbais
Keywords: Alzheimer’s disease; memory; Neurocognitive test; Tactile sense